Aetiological research on the health of migrants living in Germany: a systematic literature review. Issue 6 (14th June 2022) - Osei, Tracy Bonsu; Mank, Isabel; Sorgho, Raissa; Nayna Schwerdtle, Patricia; Hövener, Claudia; Fischer, Florian; Razum, Oliver; Danquah, Ina
Abstract : Background: Germany has become an important immigration country and health services need to adopt to meet the needs of an increasingly multicultural population. For public health planning, it is essential to understand the aetiology of health problems among migrant populations. The main objective was to systematically identify, evaluate and synthesise population-based studies that investigated exposure–outcome relationships among migrant groups in Germany. Methods: In November 2019, we searched PubMed and LIVIVO, and updated this search in November 2020, to identify peer-reviewed publications that fulfilled our eligibility criteria: English or German language; study on disease aetiology among major migrant groups in Germany, according to the latest microcensus; publication date from inception to 01 November 2020 and observational or experimental study designs. For quality appraisal, we used the Critical Appraisal Skills Programme checklists. Outcomes under investigation were categorised according to the WHO major disease groups, and their associations with risk factors were synthesised as a heat map. Results: Out of 2407 articles retrieved, we included 68 publications with a total number of 864 518 participants. These publications reported on cross-sectional data (n=56), cohort studies (n=11) and one intervention study. The population groups most frequently studied were from the Middle East (n=28), Turkey (n=24), sub-Saharan Africa (n=24), Eastern Europe (n=15) and the former Soviet Union (n=11). The outcomes under study were population group specific. There were consistent associations of demographic and socioeconomic factors with ill health among migrants in Germany. Discussion: In this systematic review, we observed low risk of bias in two-thirds of the studies. There is an increasing body of evidence for aetiological research on migrants' health in Germany. Still, the directions of associations between a wide range of risk factors and major disease groups seem only partially understood. PROSPERO registration number: CRD42018085074.